2017
DOI: 10.1177/1010428317701653
|View full text |Cite
|
Sign up to set email alerts
|

Rap2B promotes angiogenesis via PI3K/AKT/VEGF signaling pathway in human renal cell carcinoma

Abstract: Human renal cell carcinoma which is a highly vascular tumor is the leading cause of death from urologic cancers. Angiogenesis has a pivotal role in oncogenesis and in the viability and expansion of renal cell carcinoma. Rap2B, as a small guanosine triphosphate-binding protein of the Ras family, was first discovered in the early 1990s during the screening of a platelet complementary DNA library. Previous studies have shown that Rap2B aberrantly expressed in human carcinogenesis and promoted the development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
(53 reference statements)
2
18
0
Order By: Relevance
“…This pathway is a promising drug target. 33 37 In this research, we found that silencing CAV2 inhibited the expression of EGFR, PI3K and p-AKT in vitro and in vivo. We also found that the expression of CAV2 was positively correlated with EGFR, PI3K and AKT.…”
Section: Discussionmentioning
confidence: 67%
“…This pathway is a promising drug target. 33 37 In this research, we found that silencing CAV2 inhibited the expression of EGFR, PI3K and p-AKT in vitro and in vivo. We also found that the expression of CAV2 was positively correlated with EGFR, PI3K and AKT.…”
Section: Discussionmentioning
confidence: 67%
“…MiR-105 acts as a tumor suppressor or an oncogene, depending on the particular tumor context and base-pairing genes. RAP2B , a member of the GTP-binding proteins, is generally increased in many types of tumors such as glioma 23 , colorectal cancer 24 , and renal cell carcinoma 19 . We predicted that RAP2B may be a potential target of miR-105 by bioinformatics analysis ( http://www.targetscan.org/ ).…”
Section: Discussionmentioning
confidence: 99%
“…The RAP2B gene belongs to the RAS oncogene superfamily. Current research on RAP2B shows that it mainly plays a role as a cancer-promoting factor in a variety of diseases, and plays an important role in the migration and invasion of tumor cells such as lung cancer 18 , renal cell carcinoma 19 , and prostate cancer 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the PI3K/AKT/mTOR signaling pathway directly regulates specific gene expression by affecting downstream protein kinases, such as apoptosis-associated cellular molecules, including caspase-3, caspase-9, Bcl-2 and Bax, cell cycle-associated factors, including cyclin D1 and E, and by participating in the regulation of cell proliferation and apoptosis (47,48). In addition, activation of the PI3K/AKT signaling pathway promotes VEGF synthesis (49) and VEGF binds to its receptor to feedback activation of PI3K. Activation of PI3K/AKT and VEGF further promote MMP expression and mediate tumor cell infiltration and metastasis (50).…”
Section: Discussionmentioning
confidence: 99%